2015
DOI: 10.1002/cbic.201500441
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility versus Rigidity for Orally Bioavailable Cyclic Hexapeptides

Abstract: Cyclic peptides and macrocycles have the potential to be membrane permeable and orally bioavailable, despite often not complying with the "rule of five" used in medicinal chemistry to guide the discovery of oral drugs. Here we compare solvent-dependent three-dimensional structures of three cyclic hexapeptides containing d-amino acids, prolines, and intramolecular hydrogen bonds. Conformational rigidity rather than flexibility resulted in higher membrane permeability, metabolic stability and oral bioavailabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 24 publications
(12 reference statements)
1
66
0
Order By: Relevance
“…The occurrence of intramolecular hydrogen bonds in cyclic peptides also depends on the overall backbone conformation of the peptide. Nielsen et al (39) studied cyclic hexapeptides with different number of proline residues in the peptide sequence. Their study suggested that cyclic hexapeptides without a proline have relatively flexible backbone conformations in solution compared with cyclic peptide with prolines.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of intramolecular hydrogen bonds in cyclic peptides also depends on the overall backbone conformation of the peptide. Nielsen et al (39) studied cyclic hexapeptides with different number of proline residues in the peptide sequence. Their study suggested that cyclic hexapeptides without a proline have relatively flexible backbone conformations in solution compared with cyclic peptide with prolines.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings suggested that membrane permeability of cyclic peptides due to passive transport might be governed by intramolecular hydrogen bonding, steric protection of the amide NH group from solvation, and conformational flexibility allowing the peptide to assume a conformation in a hydrophobic environment, such as the center of a lipid bilayer, different from that in water. However, a more recent study by Fairlie's group showed that conformational rigidity rather than flexibility results in higher membrane permeability . Kessler's group synthesized a collection of cyclo[ d ‐ala‐(Ala) 5 ] with different N‐methylation patterns.…”
Section: Introductionmentioning
confidence: 99%
“…However, a drawback often associated with peptides is a short half‐life due to a lack of proteolytic stability. One way to improve the stability of a peptide is through backbone or side chain cyclization, as this reduces susceptibility to proteases and, in some cases, improves activity (Clark et al, ) and potentiates orally delivered activity (Clark et al, ; Nielsen et al, ; Wang et al, ). One class of peptides that has gained particular interest is venom‐derived disulfide‐rich peptides due to their inherent stability (brought about by the high number of cysteine residues) and ability to selectively and potently inhibit voltage‐gated potassium (K V ), calcium (Ca V ), and sodium (Na V ) channels.…”
Section: Introductionmentioning
confidence: 99%